A Review on the Important Key Properties of Mathematical Models Describing Photovoltaic/Thermal (PV/T) Solar Collectors System - Husain, S.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Solar energy is one of the most environmentally friendly renewable energy. There are several solar energy systems that have been studied and one of the studies made is to combine solar energy systems, which aims to optimize the energy efficiency. Photovoltaic/thermal solar collector; also known as hybrid solar collector, combines photovoltaic solar cells which convert sunlight into electricity with a solar thermal collector which transfer the wasted heat from the photovoltaic module to a heat transfer fluid. The hybrid technology has shown higher overall energy efficiency than solar photovoltaic or solar thermal alone. The target of this book is to review and present the use of important key properties of mathematical models that describe the PV/T solar collector system. A review on the current development of new mathematical models to achieve higher energy efficiency as well as challenges and limitations of photovoltaic/thermal solar collector system will also be presented. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.